2020
DOI: 10.2196/19007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Home Quarantine on Physical Activity Among Older Adults Living at Home During the COVID-19 Pandemic: Qualitative Interview Study

Abstract: Background Older adults and those with pre-existing medical conditions are at risk of death from severe acute respiratory syndrome coronavirus 2 (SARS CoV-2). In this period of quarantine, one of the reasons for going out is physical activity. This issue is important, as the impact of a sedentary lifestyle might be lower for children and young adults, but is far more severe for older adults. Although older adults need to stay at home because they have a higher risk of coronavirus disease (COVID-19)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
239
2
31

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(286 citation statements)
references
References 12 publications
14
239
2
31
Order By: Relevance
“…In the present study, the relation between physical activity and mental health was determined, especially since this lack of commuting and lockdown were reported to impact physical activity and wellness depending on different interactions and setting [31]. In line with others ( [32,33,34,35], mental health was found to be improve with physical activity.…”
Section: Discussionsupporting
confidence: 71%
“…In the present study, the relation between physical activity and mental health was determined, especially since this lack of commuting and lockdown were reported to impact physical activity and wellness depending on different interactions and setting [31]. In line with others ( [32,33,34,35], mental health was found to be improve with physical activity.…”
Section: Discussionsupporting
confidence: 71%
“… China Cross-sectional 7236 6–80 3952 (54.6%) High prevalence of anxiety and poor sleep quality especially on young people, healthcare workers and those who spent too much time thinking about the outbreak Mazza C et al, 2020 ( 39 ) Italy Cross-sectional 2766 18–90 1982 (71.7%) - Female gender, negative affect, and detachment were associated with higher levels of psychological distress - Having an acquaintance infected with COVID-19 increased depression and stress - A history of stressful situations and medical problems raised depression and anxiety levels - Having a family member infected with COVID-19 increased anxiety - Being young and working outside domicile raised stress levels Ozamiz-Etxebarria N et al 2020[40] Spain Cross-sectional 976 18–78 (8% >60) 792 (81.1%) Higher levels of anxiety, depression and stress were observed especially in people <60 and with chronic conditions Losada-Baltar A et al 2020 ( 42 ) Spain Cross-sectional 1310 18–88 (17.3% >60) 931 (71.1%) Higher loneliness and psychological distress during the lock-down. Risk factors associated: female and negative self-perception of aging Rios-González CM et al 2020 ( 41 ) Paraguay Cross-sectional 1180 ≥18 (23.8%≥50) 608 (51.5%) Symptoms of anxious or depressive were found mainly at older people Physical health Goethals et al 2020 ( 43 ) France Qualitative 6 71–91 3 (50%) - COVID-19 pandemic has affected the number of seniors attending group PA programs - Older adults expressed the need to perform PA at home - There is a need to help older adults integrate simple and safe ways to stay physically active in a limited space Castañeda-Babarro et al 2020 ( 44 ) Spain Cross-sectional 3800 18–64 1746 (46%) -PA decreased significantly during confinement in all population, especially the vigorous activities and walking time. I...…”
Section: Resultsmentioning
confidence: 99%
“…The impact on physical health of the social distancing was studied for two authors ( 43 , 44 ) (Table 1 ). Goethals et al ( 43 ) reported that COVID-19 pandemic has affected the number of seniors attending group physical activity programs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… China Cross-sectional 7236 6∓80 3952 (54.6%) High prevalence of anxiety and poor sleep quality especially on young people, healthcare workers and those who spent too much time thinking about the outbreak Mazza C et al, 2020 ( 39 ) Italy Cross-sectional 2766 18∓90 1982 (71.7%) - Female gender, negative affect, and detachment were associated with higher levels of psychological distress — Having an acquaintance infected with COVID-19 increased depression and stress — A history of stressful situations and medical problems raised depression and anxiety levels — Having a family member infected with COVID-19 increased anxiety — Being young and working outside domicile raised stress levels Ozamiz-Etxebarria N et al 2020[ 40 ] Spain Cross-sectional 976 18∓78 (8% >60) 792 (81.1%) Higher levels of anxiety, depression and stress were observed especially in people <60 and with chronic conditions Losada-Baltar A et al 2020 ( 42 ) Spain Cross-sectional 1310 18∓88 (17.3% >60) 931 (71.1%) Higher loneliness and psychological distress during the lock-down. Risk factors associated: female and negative self-perception of aging Rios-González CM et al 2020 ( 41 ) Paraguay Cross-sectional 1180 ≥18(23.8% ≥50) 608 (51.5%) Symptoms of anxious or depressive were found mainly at older people Physical health Goethals et al 2020 ( 43 ) France Qualitative 6 71∓91 3 (50%) - COVID-19 pandemic has affected the number of seniors attending group PA programs — Older adults expressed the need to perform PA at home — There is a need to help older adults integrate simple and safe ways to stay physically active in a limited space Castañeda-Babarro et al 2020 ( 44 ) Spain Cross-sectional 3800 18∓64 1746 (46%) -PA decreased significantly during confinement in all population, especially the vigorous activities and wa...…”
Section: Resultsmentioning
confidence: 99%